Accumulative Roll Bonding of precipitation-hardenable aluminum alloys of the 6000 series in a warm rolling process - Merklein, Marion; Herrmann, Jürgen (Proc. ROLLING Conference, 2016)
In several industrial fields there is a persistent trend to lightweight construction. An auspicious possibility to cope with this challenge is the application of high strength aluminum, produced by accumulative roll bonding (ARB). Key idea of the ARB approach, which was originally invented by Saito et al. (1998), is the subsequent stacking and rolling of sheet material in order to gain an ultrafine-grained microstructure. The grain refinement results from the high deformations and shear stresses during each cycle of ARB. At the moment aluminum alloys of the 6000 series are pre-heated and rolled at room temperature. Within this contribution sheets of an AA6014 alloy are manufactured in a warm rolling process for the first time. The aluminum sheets are characterized regarding their mechanical properties and in particular their flow behavior. Furthermore, the bond strength of the respectively last bonded layer is examined using T-peel tests. Both testing methods are carried out after two and four rolling cycles. Based on these investigations a process strategy for the production of multilayered sheets in a warm rolling process is derived.
EAM Import::2019-03-13

Effect of a Local Laser Heat Treatment on the Formability of Multi-layered 6000 Series Aluminum Alloys - Merklein, Marion; Herrmann, Jürgen (Physics Procedia, 2016)
The production of multi-layered aluminum alloys using the Accumulative Roll Bonding Process (ARB) is an auspicious possibility to fabricate nanostructured sheet material with enhanced mechanical properties. The increased strength qualifies these semi-finished products for lightweight applications in automotive industry. However, the ARB process also leads to a reduced ductility of the ultra-fine grained material. Furthermore, failure mechanisms like delamination can occur during forming operations. A local short term laser heat treatment according to the Tailor Heat Treated Blanks technology can be applied in order to enhance the formability and prevent failure. Multi-layered sheets of the aluminum alloy AA6014 were produced in a warm rolling process. The mechanical properties as well as the bond strength are investigated within this contribution using tensile tests and T-peel tests. The material characterization is carried out in dependency of the heat treatment temperature. Air bending tests in combination with a local laser heat treatment are used in order to investigate the formability of the multi-layered aluminum sheets.
EAM Import::2019-03-14

Experimental Investigation and Numerical Modeling of the Bond Shear Strength of Multi-layered 6000 Series Aluminum Alloys - Herrmann, Jürgen; Suttner, Sebastian; Merklein, Marion (Procedia Engineering, 2017)
The use of high-strength aluminum alloys is one key factor for the realization of lightweight design in industrial applications. Besides alloying, it is possible to produce high-strength sheet materials using the Accumulative Roll Bonding (ARB) process. Based on a repetitive stacking and roll bonding process, multi-layered sheets with a nanocrystalline grain structure are produced. The bond formation is created by a cold welding process due to the high pressure in the rolling gap and cracks in the oxide film of the aluminum sheet material caused by the thickness reduction. The experimental investigation of the bond strength is crucial for the assessment of the formability of the multi-layered sheet material. High bonding quality is necessary in order to prevent failure mechanisms like delamination in subsequent forming operations. Furthermore, a numerical model, which contains discrete layers over the sheet thickness as well as their bonding mechanisms will be implemented in finite element analysis. This enables a process layout for forming operations by the prediction of delamination effects. Within this investigation, an experimental test method is presented to characterize the bond shear strength of multi-layered sheet material. The use of an optical strain measurement system enables the identification of the material behavior over the sheet thickness during the shear test. For this investigation a 16-layered aluminum alloy AA6014 is used. However, the bond shear strength of the last bonded respectively middle layer of the sheet material is investigated. The 16-layered material has 15 bonds over the thickness but the one in the middle has the lowest bond strength as it was only roll bonded once compared to the others, which were rolled at least twice. The bonding mechanisms are modelled using a tiebreak contact formulation in the finite element software LS-DYNA. Concluding, the numerical model is validated by comparison with the experimental results.
EAM Import::2019-03-14

Herstellung und Umformeigenschaften hochfester mehrlagiger Aluminiumlegierungen der 6000er-Serie - Herrmann, Jürgen; Merklein, Marion (Energie / Effiziente Verarbeitung zukunftsweisender Leichtbauwerkstoffe, 2017)
LFT Import::2019-08-05 (2224)

Improvement of deep drawability of ultra-fine grained 6000 series aluminum alloy by tailored heat treatment - Herrmann, Jürgen; Merklein, Marion (Procedia Manufacturing, 2018)
Among other approaches like alloying, it is possible to increase the strength of aluminum sheet material by the application of processing techniques like Accumulative Roll Bonding. However, the ductility will be reduced, which results in a limited formability in deep drawing operations. In this context, the Tailor Heat Treated Blanks technology is a well-known approach to enhance the forming limits of conventional precipitation hardenable aluminum alloys. The local softening of a blank can be achieved by a short-term heat treatment, which causes a dissolution of the MgSi-clusters in the heat treated zones. In a subsequent deep drawing operation, the material flow can be improved from the softened towards crack-critical areas. Within this investigation, the method of Tailor Heat Treated Blanks is transferred to a multi-layered, ultra-fine grained sheet material of the aluminum alloy AA6014 in order to investigate the effect of a local short-term heat treatment on the forming limits in deep drawing. In a first step, a material characterization in dependency of different heat treatment temperatures is carried out. The strength and ductility, as well as the bond strength of the multi-layered sheets, are investigated. Concluding, the effect on the formability is examined by deep drawing experiments on cylindrical cups in combination with a local heat treatment of the outer flange area prior to the forming step. The results regarding the limiting drawing ratio are compared with a conventional sheet material in the T4 temper condition and a multi-layered sheet material without heat treatment. The investigations indicate that the drawability can be enhanced significantly by the combination of both methods.
LFT Import::2019-07-29 (2318)
Keywords: Accumulative roll bonding; Aluminum alloy; Deep drawing; Laser; Sheet metal; Tailor heat treated blanks

Investigation of different surface treatment parameters in the context of roll bonding processes - Schödel, Sandra; Herrmann, Jürgen; Merklein, Marion (18th International Conference on Sheet Metal, SHEMET 2019, 2019)
LFT Import::2019-08-05 (2367)

Kumulatives Walzplattieren : Bewertung der Umformeigenschaften mehrlagiger Blechwerkstoffe der ausscheidungshärtbaren Legierung AA6014 - Herrmann, Jürgen (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
Accumulative Roll Bonding is a well-known process for the production of semi-finished sheet material with an ultra-fine grained microstructure. Against the background of lightweight design, the increase in strength that can be achieved is a significant advantage. The industrial implementation of the process is prevented by a lack of knowledge of the material behavior of the high-strength, multi-layered sheet material in forming processes. The aim of this work is the evaluation of the forming properties of the ultra-fine grained aluminum alloy AA6014. For this purpose, the resulting material properties are examined depending on the parameters of the Accumulative Roll Bonding process. The focus is on a new approach to tempering the working rolls in the rolling process. The forming properties as well as the forming limits are analyzed based on the processes of deep drawing and bending. Finally, the well-known approach of Tailor Heat Treated Blanks technology to enhance the formability as a result of a local short-term heat treatment is transferred to the multi-layered, high-strength aluminum alloy AA6014. On the basis of the results of this work, the performance of the investigated materials for use in metal forming technology is demonstrated. Increasing the potential for lightweight construction by significantly increasing the specific strength of semi-finished sheet material can make a contribution to meeting the high requirements for future mobility concept

Leichtbauwerkstoffe für den modernen Automobilbau - Degner, Julia; Herrmann, Jürgen; Junker, Friedhelm; Berendt, Erik; Merklein, Marion (Konstruktion, 2018)
LFT Import::2019-07-29 (2296)

Manufacturing and Characterization of Multilayered 7000-Series Aluminum with Improved Corrosion Behavior Processed via Accumulative Roll Bonding - Degner, Julia; Bohm, Wolfgang; Herrmann, Jürgen; Kohler, Markus; Merklein, Marion (MATERIALS TODAY-PROCEEDINGS, 2019)
CRIS-Team WoS Importer:2019-04-12

Tailoring material properties in forming technology by a local heat treatment - Merklein, Marion; Graser, Matthias; Degner, Julia; Lechner, Michael; Herrmann, Jürgen (Advanced Metal Forming Processes in Automotive Industry, 2016)
LFT Import::2019-08-05 (2177)